Effects of lifestyle intervention by a nurse-led app on the prevention of symptoms in postpartum women: a randomized controlled trial - Liang, Yulian; Wang, Shiying; Tao, Jie; Yao, Zheng; Yao, Yongzi; Zhai, Jinguo (BMC nursing, 2025)
The incidence of postpartum symptoms such as prolonged lochia, constipation, fatigue, and depression remains high. Providing postpartum lifestyle interventions, including diet and exercise supervision, in clinical practice is challenging. A nurse-led app through diet supervision, exercise supervision and health education is a promising approach to lifestyle intervention. This randomized controlled trial evaluated the effects of lifestyle intervention through app on postpartum women from January to November 2024. Postpartum women with aged 18-45 years, experiencing a single pregnancy without complications or co-morbidities, able to understand and use basic technologies such as smartphones and mobile apps were recruited from a tertiary hospital in China. A total of 150 participants were randomly allocated (1:1) to either an intervention group (n = 75) or a control group (n = 75). Due to the nature of the app-based intervention, blinding of participants and research staff was not possible. Occurrence of postpartum constipation, prolonged lochia, pelvic floor muscle dysfunction, sleep, fatigue and depression were collected at 42 days postpartum through checking the electronic medical record system or by electronic questionnaires. Participants in the experimental and control groups were comparable at baseline. Among the 150 total participants, 61 (81.3%) and 63 (84%) successfully completed this study at 42 days postpartum after randomization. Participants in the intervention group showed the low occurrence of postpartum constipation (OR = 0.180, 95% CI: 0.038-0.857, P = 0.030) and prolonged lochia (OR = 0.220, 95% CI: 0.059-0.823, P = 0.025). Compared to the control group, participants in the intervention group showed significant improvements in sleep (P < 0.001, CI: 2.395-7.640), fatigue (P = 0.038, CI: 0.091-3.258), and depression (P < 0.001, CI: 3.686-7.896). However, there was no significant difference in the incidence of pelvic floor dysfunction between the two groups (OR = 0.719, 95% CI: 0.308-1.681, P = 0.446). Our study found that a nurse-led mHealth application lifestyle intervention is effective in preventing postpartum constipation and prolonged lochia, as well as improving postpartum depression, fatigue, and sleep quality. This suggests that combining nursing with digital health technologies in clinical work may improve accessibility and continuity of care. Clinicians can enhance the use of mHealth in their work by providing mHealth education to mothers to compensate for the lack of traditional care in the post-discharge phase. However, due to the limitations of this single-center study with a small sample size, future multicenter studies with long-term follow-up are needed to further explore the broader applicability and sustainability of this intervention. The protocol of the study was registered at ClinicalTrials.gov (ChiCTR2300077685) on November 16, 2023.